2009
DOI: 10.1002/asna.200911236
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic survey of emission line B‐type stars with FORS 1 at the VLT

Abstract: We report the results of our search for magnetic fields in a sample of 16 field Be stars, the binary emission-line B-type star υ Sgr, and in a sample of fourteen members of the open young cluster NGC 3766 in the Carina spiral arm. The sample of cluster members includes Be stars, normal B-type stars and He-strong/He-weak stars. Nine Be stars have been studied with magnetic field time series obtained over ∼1 hour to get an insight into the temporal behaviour and the correlation of magnetic field properties with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 26 publications
(38 reference statements)
2
39
0
Order By: Relevance
“…For instance, McSwain (2008) observed the normal B stars NGC 3766 MG 111 and NGC 3766 MG 176, and the Be star NGC 3766 MG 200, and reported no field detection. Using the same data, Hubrig et al (2009b) reported new field detections for all three stars. iii) Inconsistencies between the analysis of the same FORS dataset performed by the same authors but at different epochs.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, McSwain (2008) observed the normal B stars NGC 3766 MG 111 and NGC 3766 MG 176, and the Be star NGC 3766 MG 200, and reported no field detection. Using the same data, Hubrig et al (2009b) reported new field detections for all three stars. iii) Inconsistencies between the analysis of the same FORS dataset performed by the same authors but at different epochs.…”
Section: Introductionmentioning
confidence: 93%
“…Between them, these surveys have included more than 40 Be and possible Be stars, of which 10 stars were reported to have weak but significant magnetic fields. The reports by Hubrig et al (2007b) and Hubrig et al (2009b) suggest that weak (∼100 G) fields may be ubiquitous in Be stars, a result that would have important consequences for modelling the Be phenomenon.…”
Section: Classical Be Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among this sample the detections of a magnetic field were achieved in 8 stars, most of them just occasionally on single nights (Hubrig et al 2007;2009a;2009b). The magnetic fields of Be stars appear to be very weak, generally of the order of 100G and less.…”
Section: Resultsmentioning
confidence: 99%
“…Claims that a significant fraction of classical Be stars may indeed be magnetic have been put forward based on low-resolution spectropolarimetric studies using FORS (Hubrig, North & Schöller 2007;Hubrig et al 2009;Yudin et al 2011). Although these results were later shown to be spurious (Bagnulo et al 2012), they nonetheless motivated further study.…”
Section: Be Stars and Decretion Disksmentioning
confidence: 99%